Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

is it possible to find general solution of the recurrence relation such as

$a_{n}=a_{n-1}+A\centerdot \cos(a_{n-1})$

where $a_{0}=0$ and $A \ll 1$

EDIT: At least for

$a_{n}=a_{n-1}+A - \frac{A}{2!}\centerdot a^2_{n-1} + \frac{A}{4!}\centerdot a^4_{n-1}$

where cosine is expanded with Taylor Series with 3 terms

share|cite|improve this question
I'd be surprised. – joriki Apr 10 '12 at 9:54
Hi, @joriki so it is not possible? – mergenchik Apr 10 '12 at 9:58
If I knew how to prove that it's not possible, I would have said so. I would just be rather surprised because the relation has $a_{n-1}$ both inside and outside a transcendental function, which is usually a sign of intractability. But I've been surprised before :-) – joriki Apr 10 '12 at 10:02
Then this is not the recurrence relation which you consider in your post. // On the other hand, to show that, for every $0\lt A\leqslant1$, $a_n\to\pi/2$ when $n\to\infty$ is standard. – Did Apr 10 '12 at 10:26
To understand @joriki's and J.M.'s cautious words, consider the (nonlinear) logistic recurrence relation $x_{n+1}=4x_n(1-x_n)$ with $0\leqslant x_0\leqslant1$. But this is the exception that proves the rule, as the saying goes. – Did Apr 10 '12 at 10:37

Since the comments above led to the concluson that good approximation(s) was something the OP was after, here are some.

Let $f:a\mapsto a+A\cdot\cos(a)$ and assume that $0\lt A\leqslant1$. Then $f$ is increasing on $[0,\pi/2]$ and $f(a)\gt a$ for every $a$ in $[0,\pi/2)$ hence the sequence $(a_n)$ defined by $a_0=0$ and $a_{n+1}=f(a_n)$ for every $n\geqslant0$ is increasing with limit $\pi/2$.

Let $b_n=(\pi/2)-a_n$, then $b_0=\pi/2$, $(b_n)$ is decreasing to the limit $0$ and $b_{n+1}=b_n-A\cdot\sin(b_n)$.

Since $b_n=o(1)$, $\sin(b_n)=b_n+o(b_n)$ and $b_{n+1}=(1-A)\cdot b_n+o(b_n)$. Assume first that $\color{red}{0\lt A\lt1}$. Then a simple recursion yields $$ \frac{b_n}{(1-A)^n}=B-\frac{A}{1-A}B_n,\quad B=\sum_{k=0}^{+\infty}\frac{b_k-\sin(b_k)}{(1-A)^k},\quad B_n=\sum_{k=n}^{+\infty}\frac{b_k-\sin(b_k)}{(1-A)^k}. $$ Since $\sin(b)=b-\frac16b^3+o(b^3)$ when $b\to0$, one can show that $B$ converges and that $B_n$ is at most of order $(1-A)^{2n}$. Hence, with the finite $\color{red}{B\gt0}$ defined above, $$ \color{red}{a_n=(\pi/2)-B\cdot(1-A)^n+O((1-A)^{3n})}. $$ When $\color{blue}{A=1}$, $b_{n+1}=b_n-\sin(b_n)\sim\frac16b_n^3$ and one can show that $\log b_n=-c\cdot3^n+o(3^n)$ for some finite positive $c$, hence there exists some $\color{blue}{0\lt C\lt1}$ such that $$ \color{blue}{a_n=(\pi/2)-C^{3^n+o(3^n)}}. $$

share|cite|improve this answer
couldn't catch after $b_{n+1} = b_{n} - A\cdot \sin(b_{n})$. Verified that $a_{n}+b_{n}=\pi/2$ for $0\lt A \lt 1$ with program :). Couldn't understand this line "Since $b_n=o(1), sin(b_n)=b_n+o(b_n)$" – mergenchik Apr 10 '12 at 14:19
If $a_{n+1}=a_n+A\cos(a_n)$ and $b_n=(\pi/2)-a_n$, $b_{n+1}=(\pi/2)-a_n-A\cos(a_n)$ and $\cos(a_n)=\sin(b_n)$ hence $b_{n+1}=b_n-A\sin(b_n)$. // How one can verify that $a_n+b_n=\pi/2$ (with a program!?) since this is the definition of $b_n$ somewhat baffles me. // When $x=o(1)$ (that is, $x\to0$), $\sin(x)=x+o(x)$. Since $b_n=o(1)$, $\sin(b_n)=b_n+o(b_n)$. – Did Apr 10 '12 at 14:43
:D sorry. My brain stopped since thinking for a long time for this problem. – mergenchik Apr 10 '12 at 14:47
will $B$ converge? As $k\to +\infty$ then $b_k - \sin(b_k) \to \pi /2$ but since $A\lt1$ then $(1-A)^k \to 0$. or I'm missing something? – mergenchik Apr 10 '12 at 15:06
Yes $B$ converges. Proof: Since $b_n\to0$ and $b_{n+1}=(1-A)b_n+o(b_n)$, for every $1-A\lt F\lt1$, $b_{n+1}\leqslant Fb_n$ for $n$ large enough. Hence $b_n\leqslant cF^n$ and $b_n-\sin(b_n)\leqslant\frac16b_n^3\leqslant c'F^{3n}$. Choosing $F\gt1-A$ such that $F^3\lt1-A$, one sees that $B$ converges. End of the proof. – Did Apr 10 '12 at 15:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.